Options for Financing Lifelong Learning - Palacios, Miguel (World Bank, Washington, DC, 2014)
How should lifelong learning be financed? The author attempts to answer the question by creating a framework for analyzing different education financing mechanisms in light of particular characteristics of lifelong learning. The framework compares the different financing alternatives on four dimensions: (1) who ultimately pays for the education, (2) who finances its immediate costs, (3) how payments are made, and (4) who collects the payments. The author uses specific characteristics of lifelong learning to determine which among the financing alternatives are most useful. The characteristics are that the individual should decide what and where to study, carry a significant part of the financial burden, and be encouraged to continue learning through all life stages. The author analyzes the financing alternatives according to who ultimately pays for the education. Hence, the alternatives are classified either as cost-recovery or cost-subsidization alternatives. Cost-recovery alternatives include traditional loans, a graduate tax, human capital contracts, and income-contingent loans. Subsidization alternatives are those in which the state directly subsidizes institutions or in which the state gives vouchers to students. The author concludes that combining income-contingent loans and human capital contracts with vouchers is the most efficient and equitable method for financing lifelong learning. The author discusses the role of governments and multilateral organizations in improving the financing of lifelong learning. He assesses shifting toward cost-recovery alternatives, focusing on collection of payments, and aiming for the involvement of private capital as key issues that should be addressed to ensure that lifelong learning will be available for all equitably and efficiently.